A Homozygous [Cys25]PTH(1‐84) Mutation That Impairs PTH/PTHrP Receptor Activation Defines a Novel Form of Hypoparathyroidism. (8th June 2015) - Lee, Sihoon; Mannstadt, Michael; Guo, Jun; Kim, Seul Min; Yi, Hyon‐Seung; Khatri, Ashok; Dean, Thomas; Okazaki, Makoto; Gardella, Thomas J; Jüppner, Harald
ABSTRACT Hypocalcemia and hyperphosphatemia are encountered in idiopathic hypoparathyroidism (IHP) and pseudohypoparathyroidism type Ib (PHP1B). In contrast to PHP1B, which is caused by resistance toward parathyroid hormone (PTH), the genetic defects leading to IHP impair production of this important regulator of mineral ion homeostasis. So far, only five PTH mutations were shown to cause IHP, each of which is located in the hormone's pre‐pro leader segment and thus impair hormone secretion. In three siblings affected by IHP, we now identified a homozygous arginine‐to‐cysteine mutation at position 25 (R25C) of the mature PTH(1‐84) polypeptide; heterozygous family members are healthy. Depending on the assay used for evaluating these patients, plasma PTH levels were either low or profoundly elevated, thus leading to ambiguities regarding the underlying diagnosis, namely IHP or PHP1B. Consistent with increased PTH levels, recombinant [Cys25]PTH(1‐84) and wild‐type PTH(1‐84) were secreted equally well by transfected COS‐7 cells. However, synthetic [Cys25]PTH(1‐34) was found to have a lower binding affinity for the PTH receptor type‐1 (PTH1R) than PTH(1‐34) and consequently a lower efficiency for stimulating cAMP formation in cells expressing this receptor. Consistent with these in vitro findings, long‐term infusion of [Cys25]PTH(1‐34) resulted only in minimal calcemic and phosphaturic responses, despite readily detectable levels of [Cys25]PTH(1‐34) in plasma. The mineral ion abnormalities observed in the three IHP patients are thus most likely caused by the inherited homozygous missense PTH mutation, which reduces bioactivity of the secreted hormone. Based on these findings, screening for PTH(1‐84) mutations should be considered when clinical and laboratory findings are consistent with PHP1B, but GNAS methylation changes have been excluded. Differentiating between IHP and PHP1B has considerable implications for genetic counseling, therapy, and long‐term outcome because treatment of IHP patients with inappropriately high doses of active vitamin D and calcium can contribute to development of nephrocalcinosis and chronic kidney disease. © 2015 American Society for Bone and Mineral Research.